Acute interstitial nephritis with Prothionamide. (May 2022) - Asnake, Molla; Henock, Andualem; Abayneh, Menigistu; Getu, Shimelis; Hailemariam, Shewangizaw; Endalkachew, Biruk; Zerihun, Dessalegn
Among drug-related complications, drug-related nephrotoxicity is the commonest. It is the cause for 7% of all drug-related toxicities among inpatients and accounts for 20% to 30% of acute renal failure. Acute interstitial nephritis is one of the drug-related adverse reactions and occurs due to a drug-related type 4 hypersensitivity reaction. In this case report, we reported acute interstitial nephritis that causes acute renal failure (acute kidney injury) in a patient taking Prothionamide therapy. This drug-related side effect had not been reported. In this case report, we report a patient who develops fatigability, rash, and intermittent fever after 14 days of taking the drug Prothionamide. The main aims of this case report are to use it as a pharmacovigilance report for drug-producing companies and to consider a further study on this side effect. It is also an alert for clinicians to consider this side effect when patients develop acute interstitial nephritis while taking Prothionamide.